Management of import substitution policy implementation in the industrial (regional) and financial sectors of the Rostov region economy - S. A. Anesyants; N. A. Kuryanov (Новые технологии)
The article presents the main directions for the implementation of the policy of import substitution at the regional level on the example of the Rostov region. The main directions and tools for supporting the policy of import substitution by regional authorities and management are analyzed.